Morphological Features of the Acupuncture Points of Bladder Meridian in the Giant Anteater (Myrmecophaga tridactyla) - Marques, Gustavo de Calasans [UNESP] (2020)
Background: The acupuncture points are considered a point in the skin of sensitivity to stimulation. The acupuncture meridians represent the communication between acupuncture points and internal organs. The giant anteater (Mirmecophaga tridactyla) is routinely attended in veterinary centers, and is pivotal to know its morphology and therapies such as acupuncture that, probably, can be used in medical practice. Thus, the aim of this study was to evaluate the morphological substrate in regions that correspond to the transposition of acupuncture points of the Bladder Meridian using radiography, ultrasonography, electrical impedance and histology in the giant anteater. Materials, Methods & Results: Seven giant anteaters (six males and one female) were used. The animals were from the Center of Medicine and Research in Wild Animals (CEMPAS), School of Veterinary Medicine and Animal Science, UNESP, Botucatu, Sao Paulo. The acupoints of Bladder Meridian evaluated were Bladder 11 (B-11), Bladder 18 (B-18), Bladder 23 (B-23), Bladder 25 (B-25), and Bladder 28 (B-28). The locations of the acupoints were transposed based on the location of these acupuncture points in dogs. Four animals were live and were used for radiographic, ultrasonographic, and electrical impedance analysis. Three animals were died and the fragments of this acupoints were destined to histological routine with hematoxylin and eosin (HE) and Masson's Trichrome stains. The giant anteaters studied had fifteen thoracic vertebrae, three lumbar vertebrae, and five sacral vertebrae fused in a single bone. The acupuncture points were characterized by presence of abundant connective tissue at the superficial and intermuscular level, muscular fascia, and many neurovascular bundles in the dermal layer. These bundles consisted of nerves, arteries and veins of various calibers. The spaces between the nerves and blood vessels were filled by loose connective tissue containing adipose cells, capillaries, and sweat glands. Discussion: The network of acupuncture points can be seen as a representation of a network formed by interstitial connective tissue. This hypothesis is supported by ultrasound imaging that demonstrated plans for cleavage of connective tissue at acupuncture points in normal humans. It seems that the anatomical relationship of acupoints and meridians with connective tissue planes is relevant to the mechanism of action of acupuncture and suggests an important integrative role for interstitial connective tissue. The presence of connective tissue was observed in the transposition areas studied in the giant anteater using ultrasound. The main histological structures found in the transposition regions of the acupoints in the giant anteater were the nerve and connective tissue, similar to other studies, who claimed that the nerve is the main histological component of an acupoint. Therefore, there are reports suggesting that the network of acupoints and meridians can be seen as a representation of a network formed by interstitial connective tissue and that this relationship is important for the therapeutic mechanism of acupuncture. Based on the results of this study, it is possible to infer that the studied regions present a morphological substrate that is consistent with the characteristics of an acupuncture point. Thus, it is suggested that there are probably acupuncture points in these regions in the giant anteater, which makes possible the use of this alternative medical therapy for the treatment of these animals.